Sequence‐Based Multi Ancestry Association Study Reveals the Polygenic Architecture of Varroa destructor Resistance in the Honeybee Apis mellifera - Sonia E. Eynard; Fanny Mondet; Benjamin Basso; Olivier Bouchez; Yves Le Conte; Benjamin Dainat; Axel Decourtye; Lucie Genestout; Matthieu Guichard; François Guillaume; Emmanuelle Labarthe; Barbara Locke; et al. (Molecular Ecology, 2025)
Honeybees, Apis mellifera , have experienced the full impacts of globalisation, including the recent invasion by the parasitic mite Varroa destructor , now one of the main causes of colony losses worldwide. The strong selection pressure it exerts has led some colonies to develop defence strategies conferring some degree of resistance to the parasite. Assuming these traits are partly heritable, selective breeding of naturally resistant bees could be a sustainable strategy for fighting infestations. To characterise the genetic determinism of varroa resistance, we conducted the largest genome wide association study performed to date on whole genome sequencing of more than 1500 colonies on multiple phenotypes linked to varroa resistance of honeybees. To take into account some genetic diversity of honeybees, colonies belonging to different ancestries representing the main honeybee subspecies in Western Europe were included and analysed both as separate populations and combined in a meta‐analysis. The results show that varroa resistance is substantially heritable and polygenic: while 60 significant associations were identified, none explain a substantial part of the trait genetic variance. Overall our study highlights that genomic selection for varroa resistance is promising but that it will not be based on managing a few strong effect mutations and rather use approaches that leverage the genome wide diversity of honeybee populations. From a broader perspective, these results point the way towards understanding the genetic adaptation of eusocial insects to parasite load.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Determining Objective Parameters to Assess Gait Quality in Franches-Montagnes Horses for Ground Coverage and Over-Tracking - Part 2: At Trot - Annik Imogen Gmel; Eyrún Halla Haraldsdóttir; Filipe Manuel Serra Bragança; Antonio M Cruz; Markus Neuditschko; Michael Andreas Weishaupt (Journal of Equine Veterinary Science, 2023)

Cancer-associated fibroblast-derived WNT2 increases tumor angiogenesis in colon cancer - Daniela Unterleuthner; Patrick Neuhold; Katharina Schwarz; Lukas Janker; Benjamin Neuditschko; Harini Nivarthi; Ilija Crncec; Nina Kramer; Christine Unger; Markus Hengstschläger; Robert Eferl; Richard Moriggl; et al. (Angiogenesis, 2020)
WNT2 acts as a pro-angiogenic factor in placental vascularization and increases angiogenesis in liver sinusoidal endothelial cells (ECs) and other ECs. Increased WNT2 expression is detectable in many carcinomas and participates in tumor progression. In human colorectal cancer (CRC), WNT2 is selectively elevated in cancer-associated fibroblasts (CAFs), leading to increased invasion and metastasis. However, if there is a role for WNT2 in colon cancer, angiogenesis was not addressed so far. We demonstrate that WNT2 enhances EC migration/invasion, while it induces canonical WNT signaling in a small subset of cells. Knockdown of WNT2 in CAFs significantly reduced angiogenesis in a physiologically relevant assay, which allows precise assessment of key angiogenic properties. In line with these results, expression of WNT2 in otherwise WNT2-devoid skin fibroblasts led to increased angiogenesis. In CRC xenografts, WNT2 overexpression resulted in enhanced vessel density and tumor volume. Moreover, WNT2 expression correlates with vessel markers in human CRC. Secretome profiling of CAFs by mass spectrometry and cytokine arrays revealed that proteins associated with pro-angiogenic functions are elevated by WNT2. These included extracellular matrix molecules, ANG-2, IL-6, G-CSF, and PGF. The latter three increased angiogenesis. Thus, stromal-derived WNT2 elevates angiogenesis in CRC by shifting the balance towards pro-angiogenic signals.